Comparison of Ultrasound Guided Transversus Abdominis Plane Block Versus Local Wound Infiltration for Post Operative Analgesia in Patients Undergoing Gynaecological Surgery Under General Anaesthesia - Ranjit, S; Shrestha, SK (Kathmandu University Medical Journal, 2015)
Background Transversus abdominis plane block has been recently developed as a part of multimodal post operative analgesic techniques. We compared the analgesic efficacy of this technique with local bupivacaine infiltration in patients undergoing gynaecological surgeries with pfannenstiel incision and lower midline incision under general anaesthesia. Objectives To evaluate the efficacy of ultrasound guided transversus abdominis plane block for postoperative analgesia. Methods Patients were randomly allocated to three groups: control group (n=15), transversus abdominis plane block group (n=15), who received bilateral transversus abdominis plane blockwith 0.25% bupivacaine, and local infiltration group (n=15), who received local wound infiltration with 0.25% bupivacaine at the end of surgery. All patients received intramuscular diclofenac 12 hourly and intravenous tramadol SOS in the postoperative period. Visual analogue scores for pain were assessed at 1,2,4,8,12 and 24 hours postoperatively and these were compared between the three groups. Average tramadol consumption in 24 hours were also compared among the three groups. Data were subjected to univariate ANOVA test and chi-square test. Level of significance was set at 0.05. Results Visual analogue scores were significantly less in transversus abdominis plane block group and effect lasted up to 12 hours at rest postoperatively and 8 hours during cough and movement. Conclusion Bilateral Transversus abdominis plane block was effective in reducing postoperative pain scores for 8 to 12 hours postoperatively. This block was also successful in reducing postoperative opioid requirement. Kathmandu University Medical Journal Vol.12(2) 2014: 93-96